THE INTERNATIONAL HUMAN RIGHT TO HOUSING & THE CANADIAN CHARTER: A CASE COMMENT ON TANUDJAJA V. CANADA (ATTORNEY GENERAL) - David DesBaillets (The Windsor Yearbook of Access to Justice, 2015)
The case of Tanudjaja v. Attorney General, represents an unprecedented opportunity for Canadian legal scholars to examine the right to adequate housing in the Canadian human rights context. It is the only legal challenge that broaches directly the right to housing under Canadian law, basing its arguments on two key elements contained in Charter of Rights and Freedoms: sections 7 and 15. Moreover, the case represents an attempt by the claimants to bolster their Charter claim with reference to housing rights found in international human right’s law. For Canadian housing rights’ scholars, this decision, though ultimately quite negative in its conclusions, demonstrates the need for a better understanding of the intersection between international legal norms on human rights on the one hand, and the Charter, on the other. It does not, however, adequately portray the full extent of the former’s influence on the latter, as Justice Lederer of the Ontario Superior Court of Justice, failed to address the importance of international legal doctrine with respect to the interpretation of positive social and human rights in the Canadian legal context. In particular, he ignored the growing body of Charter related cases and precedents in Canadian jurisprudence that shed light on the complex relationship between fundamental human rights enshrined in various international legal documents and the recognized positive obligations they impose on the government of Canada to implement them under such long established treaties as the Covenant of Economic Social and Cultural Rights.